2022
DOI: 10.1186/s12862-021-01958-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between male secondary sexual traits, physiological state and offspring viability in the three-spined stickleback

Abstract: Background Sexual signals produced by males play a central role in sexual selection, but the relationship between these traits and the quality of the bearer are often ambiguous. Secondary sexual traits may represent genetic quality of the bearer, resulting in positive relationships with physiological state, or may be costly to produce, showing trade-off with physiological state. A number of studies have explored the relationships between secondary sexual traits and other functional traits, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 88 publications
(83 reference statements)
5
4
0
Order By: Relevance
“…Male yellowness never predicted offspring performance in the direction that would be expected from ‘good genes’ hypotheses of sexual selection. This is in line with recent findings on three-spined stickleback ( Gasterosteus aculeatus ) where male coloration could not be linked to offspring viability [46].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Male yellowness never predicted offspring performance in the direction that would be expected from ‘good genes’ hypotheses of sexual selection. This is in line with recent findings on three-spined stickleback ( Gasterosteus aculeatus ) where male coloration could not be linked to offspring viability [46].…”
Section: Discussionsupporting
confidence: 92%
“…Male yellowness never predicted offspring performance in the direction that would be expected from 'good genes' hypotheses of sexual selection. This is in line with recent findings on three-spined stickleback (Gasterosteus aculeatus) where male coloration could not be linked to offspring viability [46]. Mating systems that are not based on resources, like those of salmonids, are a challenge to evolutionary biologists because female choice is expected to lead to increased offspring survival ('good genes') or increased attractiveness of sons [47].…”
Section: Discussionsupporting
confidence: 82%
“…We conclude that if females could choose their mate, they would profit most from avoiding genetic similarity while ignoring male coloration to achieve the highest genetic benefit from mate choice. Analogous negative effects of genetic similarity were recently demonstrated in an amphibian (Byrne et al 2021 ), and analogous non-significant effects of male coloration on offspring viability were recently reported for three-spined stickleback ( Gasterosteus aculeatus ) (Chiara et al 2022 ).…”
Section: Discussionsupporting
confidence: 64%
“…This increase in courtship could be a signal of male quality as has been suggested in other studies that have reported that courtship intensity could be a stronger signal of quality than the presence of eggs in a male's nest that act as a primer for males to court more (Jamieson & Colgan, 1989 ). Similarly, males who court more have relatively higher offspring survival rate after hatching as seen in a population from Spain (Chiara et al, 2022 ).…”
Section: Discussionmentioning
confidence: 84%
“…Common female stickleback may be more attracted to white males as common male stickleback cannot invest as much energy in courtship and nuptial colouration, as it can reduce energy reserves and decrease in egg survival as seen in a population of stickleback from California (von Hippel, 2000). However, other studies examining courtship and hatching success found that in common and 15-spine sticklebacks males who courted more had higher offspring hatch and/or survival rates (Chiara et al, 2022;Östlund & Ahnesjö, 1998) and were preferred by females (Östlund & Ahnesjö, 1998), but did not find an association between female preference or male parental ability and the size of male 15-spine sticklebacks (Östlund & Ahnesjö, 1998).…”
Section: Female Response and Male Body Sizementioning
confidence: 99%